2009
DOI: 10.1176/appi.ajp.2009.09010016
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of At-Risk and Binge Drinking Among Middle-Aged and Elderly Community Adults: National Survey on Drug Use and Health

Abstract: Objective The purpose of this article was to estimate the prevalence, distribution, and correlates of at-risk alcohol use (especially binge drinking) among middle-aged and elderly persons in the United States and to compare at-risk alcohol use between women and men. Method Secondary analysis of the 2005 and 2006 National Survey on Drug Use and Health was conducted for 10,953 respondents aged 50 years and older. Among respondents, 6,717 were 50 to 64 years of age and 4,236 were ≥65 years. Social and demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
250
10
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(295 citation statements)
references
References 19 publications
25
250
10
10
Order By: Relevance
“…12 In a study using 2005 and 2006 data from the National Survey on Drug Use and Health, 13 % of men and 8 % of women aged 65 and older reported drinking two or more drinks per day. 13 Although low to moderate levels of alcohol use can have health benefits, [14][15][16][17][18] the exact benefit dose is not known and may not be risk free. [19][20][21][22] While alcohol consumption within guidelines may be permissible in some individuals with diabetes and cardiovascular disease, alcohol is not advised with certain prescription medications and can cause serious consequences.…”
Section: Introductionmentioning
confidence: 99%
“…12 In a study using 2005 and 2006 data from the National Survey on Drug Use and Health, 13 % of men and 8 % of women aged 65 and older reported drinking two or more drinks per day. 13 Although low to moderate levels of alcohol use can have health benefits, [14][15][16][17][18] the exact benefit dose is not known and may not be risk free. [19][20][21][22] While alcohol consumption within guidelines may be permissible in some individuals with diabetes and cardiovascular disease, alcohol is not advised with certain prescription medications and can cause serious consequences.…”
Section: Introductionmentioning
confidence: 99%
“…En conjunto, los inhalantes, alucinógenos, metanfetaminas y la heroína representaron un consumo por debajo del 0.2%. 21,26 El consumo de sustancias en adultos mayores de la Ciudad de México es menor cuando se compara con los resultados para la población de adultos (18 y 65 años) de la última Encuesta Nacional de Adicciones (ENA-2011) (Anexo 1). El consumo de alcohol alguna vez en la vida en la ENA en población adulta (77.1%) 2 fue 11.8% más alto en comparación con la estimación que se obtuvo en el presente estudio.…”
unclassified
“…Nevertheless, the expectation that both can be reduced was confirmed in a pilot clinical trial to test the efficacy of an intervention aimed at decreasing both (Ames et al, 2014) in which it was observed that when the treatment was realized simultaneously and was also focused on smoking, after three and six months the patients continued not to smoke and also reduced the consumption of alcohol. Therefore, and despite the heterogeneous nature of these results, the existence of a special relationship between smoking and binge drinking appears to be consistent (Blazer and Wu, 2009). In our sample, the subjects at greater risk of continuing harmful alcohol use were smokers of 25 or more cigarettes per day, followed by ex-smokers and finally smokers of fewer than 10 cigarettes per day.…”
Section: Discussionmentioning
confidence: 81%